2004
DOI: 10.1210/me.2002-0282
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical Tumorigenesis in Transgenic Mice Expressing the Inhibin α-Subunit Promoter/Simian Virus 40 T-Antigen Transgene: Relationship between Ectopic Expression of Luteinizing Hormone Receptor and Transcription Factor GATA-4

Abstract: We have analyzed the ontogeny and putative mechanisms of transregulation of LH receptor (LHR) and transcription factor GATA-4, coexpressed during the adrenocortical tumorigenesis of prepubertally gonadectomized transgenic (TG) mice expressing the inhibin alpha-subunit promoter/simian virus 40 T-antigen (inhalpha/Tag) transgene. The onset of adrenal LHR mRNA and protein expression coincided with that of GATA-4 at the age of 4 months and preceded the appearance of discernible adrenal tumors at about 6 months. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…As these mice have earlier been extensively characterized (Kananen et al 1996a, Rahman et al 2001, the discernible adrenocortical tumors appear at the age of 6 months with 100% penetrance. We started all the treatments at the age of 6.5 months, in order to make sure that any treatment effect will be only due to the anti-tumoral effect, but not by prevention of the tumor development.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…As these mice have earlier been extensively characterized (Kananen et al 1996a, Rahman et al 2001, the discernible adrenocortical tumors appear at the age of 6 months with 100% penetrance. We started all the treatments at the age of 6.5 months, in order to make sure that any treatment effect will be only due to the anti-tumoral effect, but not by prevention of the tumor development.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…In previous studies, we showed an apparent positive and reciprocal feed-forward amplification link between GATA-4 and luteinizing hormone/human chorionic gonadotropin receptor (LHCGR/LHR) expression during adrenocortical tumorigenesis in humans and mice (Kananen et al, 1996;Bielinska et al, 2003;Rahman et al, 2004). However, it remains unknown how GATA-4 and LHCGR convene their activities in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Wild-type (WT) murine adrenal glands do not express detectable levels of LHCGR, whereas exceptional conditions such as chronically elevated serum LH levels (e.g. GDX) can induce its expression (Rilianawati et al, 1998;Kero et al, 2000;Rahman et al, 2004). Aberrant LHCGR expression in the adrenal cortex has been reported in women with transient Cushing syndrome during pregnancy and persistent Cushing syndrome after menopause, both associated with elevated serum levels of hCG or LH (Guilhaume et al, 1992;Pabon et al, 1996;Lacroix et al, 1999;Mijnhout et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor GATA-4 has emerged as a potent activator of several genes expressed in endocrine tissues, including anti-Müllerian hormone, aromatase, luteinizing hormone receptor, inhibin-B and inhibin- (Ketola et al 1999, Tremblay & Viger 1999, Feng et al 2000, Rahman et al 2004. GATA-4 belongs to a family of zinc-finger transcription factors, termed the GATAbinding proteins, primarily recognizing a consensus GATA motif in the promoters and enhancers of their target.…”
Section: Introductionmentioning
confidence: 99%